Implementación de un PMP para el área de producción de tolvas de la empresa metalmecánica FAMECA S.A.C - Julcamoro Lezama, Gino André (2023)
As a summary, it will begin by making a diagnosis that gives us light on the state of the machines in terms of the number of failures, measurement of the most significant indices, on the other hand, the study of the technical system and its respective subsystems should be considered. It was possible to determine, identify and quantify the unexpected events that occurred between January and December of the year 2020, when evaluating the failures that manifested themselves in the 7 selected equipment, it results in that 903 hours are required for repair per year, they were also registered. 110 interventions in the same period of time. When preparing the root cause diagrams of the failures in the equipment, systems and subsystems, the need for constant training for the personnel in charge can be observed, as well as the lack of basic maintenance activities. Calculating the availability, we find that the highest percentage of failures corresponds to the Welding Equipment, which reaches 24.5%, while the one with the lowest percentage of failures in the Lathe, which represents 10%. Carrying out the respective calculations we find that the Total Operating Time is 22.20 hours with an average of 3,172.57 hours, the Time for Repair is 1575 hours with an average of 225 hours, the Mean Time to Failure was calculated, which is 1432.98 hours and the respective average is 204.72 hours, on the other hand we calculated the Average Repair Time resulting in 59.94 hours and with the average of 8.56 hours, finally the Availability was calculated, which reached 596.42% with an average of 85.20. The proper monitoring of the operation of the equipment must be done using the various strategies that include, among them, the proper preparation of the root cause diagrams in the equipment. It is important to cross the information regarding the main indices such as Availability, Reliability and Maintainability to seek to improve them. Likewise, being attentive to the variation in Availability must be one of the constant tasks that the maintenance planner must master and always seek to increase, for which it is necessary to be properly trained.